Academic Senate Minutes 2014-10-23 - Academic Senate:::::::::
Chair Report. Agenda – Approved with slight modifications. Minutes of 9/25 and 10/9 amended and approved. Consent item: Advance Practice Clinical Education Certificate – Approved. Vice Chair Report. Vice President of Student Affairs Report. Associated Students Report. Statewide Senators Report. Classroom renovation report. Special Guests: Mayor of Rohnert Park, Joseph Callinan and City Manager, Darrin Jenkins. Commendation for Christopher Dinno from J. Chan. Skateboard, bicycles, etc. update from Chief of Police, Nate Johnson. SSU SETE Policy – Approved. EPC report. FSAC report. SAC Report. CFA Report. Good of the Order.